2014
DOI: 10.1177/1541931214581414
|View full text |Cite
|
Sign up to set email alerts
|

Haptic Perception of Distance-To-Break for Compliant Tissues in a Surgical Simulator

Abstract: In minimally invasive surgery (MIS), it is critical to have the ability to accurately interpret haptic information and apply appropriate force magnitudes onto soft tissue in order to minimize tissue trauma. The surgeon's administration of force onto tissue reveals useful perceptual information which guides further haptic interaction making the force perception in MIS a dynamic process. It has been hypothesized that the compliant nature of soft tissue during force application provides biomechanical information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Although Long et al (2014) were able to demonstrate that DTB can be perceived, several other factors were not taken into consideration that may affect an observer’s perception of nonlinear material break point. For example, trocars are a sealing mechanism at the incision sites during MIS that act as a portal for tools to access the body and which maintain pressure within the body cavity.…”
Section: Application In Laparoscopic Surgerymentioning
confidence: 94%
See 4 more Smart Citations
“…Although Long et al (2014) were able to demonstrate that DTB can be perceived, several other factors were not taken into consideration that may affect an observer’s perception of nonlinear material break point. For example, trocars are a sealing mechanism at the incision sites during MIS that act as a portal for tools to access the body and which maintain pressure within the body cavity.…”
Section: Application In Laparoscopic Surgerymentioning
confidence: 94%
“…Just as past research has identified the haptic invariant subserving the perception of object length and weight by wielding, we have identified DTB as a haptic invariant that specifies the immanent break point of a nonlinear material that an observer is probing or stretching (Long et al, 2014). DTB is a form of haptic “looming,” in that it is based on the increasing amount of force needed to probe into or to stretch a material with an exponential force-displacement relationship.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations